2015
DOI: 10.1002/pen.24147
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alkali treatment on flax fiber for use as reinforcements in polylactide stereocomplex composites

Abstract: The flax and equivalent proportion of poly(l‐lactic acid)/poly(d‐lactic acid) (PLLA/PDLA) were melt compounded and injection molded to prepare flax‐reinforced polylactide stereocomplex (sc‐PLA) bio‐composite, and the effect of alkali treatment on the structure and properties of flax as well as the flax/sc‐PLA composite was investigated. SEM and FTIR results showed hemicellulose in flax was almost completely removed after alkali treatment and the treated flax (ALK‐flax) bundles were more separated with a cleane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 28 publications
(44 reference statements)
0
25
1
Order By: Relevance
“…The increased interaction between the PF and the PLA matrix could further cause the fiber surface to act as nucleation sites for PLA crystallization. Consequently, the PF and PLA composites had increased crystallinity compared to those of composites reinforced with WF …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased interaction between the PF and the PLA matrix could further cause the fiber surface to act as nucleation sites for PLA crystallization. Consequently, the PF and PLA composites had increased crystallinity compared to those of composites reinforced with WF …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the WF surface was rougher than the PF surface because of the middle lamellar materials (wax, pectin, lignin, and hemicellulose) remaining on the WF surface [Figure (a)]. However, after BECMP treatment, most of the substances associated with the cellulose were removed, resulting in the smooth and clear PF surface shown in Figure (b) …”
Section: Resultsmentioning
confidence: 99%
“…It indicated that the content of PEG was increased in the reed samples after modification, and it further illustrated that the modifier penetrated well into the reed stalk. The absorption peak at 2888 cm -1 represents the stretching vibration of methylene (-CH2) (Zhang et al 2015). The intensity of the methylene absorption peak decreased after PEG modification and decreased with the increase in PEG molecular weight.…”
Section: Ft-ir Characterizationmentioning
confidence: 99%
“…Polylactic acid (PLA) has attracted considerable research interest owing to its good biocompatibility and biodegradability [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. However, its disadvantages, such as poor heat-deflection temperature (HDT: 50 °C for neat PLA) and slow crystallization rate, limit its application [ 8 , 9 , 10 , 11 , 12 , 13 ]. HDT is a crucial physical quantity used to characterize the heat resistance of polymeric materials [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%